Maize and Pea Root Interactions Promote Symbiotic Nitrogen Fixation, Thereby Accelerating Nitrogen Assimilation and Partitioning in Intercropped Pea - Yali Sun; Zefeng Wu; Falong Hu; Hong Fan; Wei He; Lianhao Zhao; Congcong Guo; Xiaoyuan Bao; Qiang Chai; Cai Zhao (Agronomy)
Cereal/legume intercropping enhances legume nodulation and improves nitrogen use efficiency (NUE) in cereal crops. This facilitation of symbiotic nitrogen fixation (SNF) in intercropped legumes involves a complex eco-physiological mechanism driven by multiple factors. Among them, interspecific root interactions (IRIs) are a key factor influencing SNF in intercropped legumes. Currently, it remains unclear whether and how IRIs modulate SNF to affect NUE and yield formation in legume species. In this study, maize/pea intercropping with different types of root separation [no barrier (NB) and plastic barrier (PB)] and pea monocropping (IP) were simulated in a nitrogen (N)-free nutrient matrix in pots, and the SNF, N metabolism, and N partitioning were investigated. We demonstrated that IRIs optimize SNF performance. N assimilation is positively regulated following increases in enzyme activity and gene expression in intercropped roots and nodules. Furthermore, IRIs facilitate amino acid (AA) export from nodules to roots and shoots, which is followed by an increase in AA levels in leaves (source) and leaf exudates (sink). Overall, intensive SNF drives N metabolism and alters source-to-sink N partitioning, thereby increasing NUE (by 23%) and yield (by 15%) in intercropped pea. This study reveals the positive roles of IRIs to the NUE and yield and provides useful reference material for increasing N contents derived from SNF to maximize NUE and crop yields in intercropped legumes.